Endobiliary radiofrequency ablation and percutaneous biliary stent placement for choledocal invasion of renal cell carcinoma - Ayaz, Ercan; Aşık, Murat (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Ayaz E, Aşık M. Endobiliary radiofrequency ablation and percutaneous biliary stent placement for choledocal invasion of renal cell carcinoma. Turk J Gastroenterol 2019; 30(9): 854-7.